Processo de sofrimento moral de enfermeiros: desafios éticos na prática profissional no contexto hospitalar - Carolina da Silva Caram (2018)
The moral distresse in health work is an emerging ethical problem. His experience reflects in the professional practice of individuals, passing organizational and managerial issues. The hospital environment, especially closed areas such as the Surgical Block and the Intensive Care Unit, is a privileged locus of experiences of moral suffering by nurses. The complexity and particularities of the work carried out in these sectors by this professional category, have important repercussions on the quality of care and on the physical and psychological conditions of the professionals. The aim of this study was to understand the moral suffering process experienced by nurses in enclosed areas of a hospital in the context of professional practice, considering the invisibility and the ethical and moral challenges. This is a study of integrated single case with a qualitative approach, developed in the surgical ward and the intensive care unit of a large hospital, private, located in the city of Belo Horizonte / MG. The participants were all nurses who work in the mentioned sectors. Data collection was conducted through individual interviews with semi-structured script and observation. The Ethics Committee of the institution and signing the Consent and Informed (IC) by the participants collected data after approval of the project. Data analysis followed the chronological poles contents of Thematic Analysis, with the help of ATLAS.ti software, under Virtue Ethics Theory. The research is relevant, given the working conditions of nurses in the hospital setting. The data showed ethical and moral aspects of the daily work of nurses who are potential triggers of moral distresse. These aspects are related to overwork, the distancing of doing that nurses conceived in training and the reality of everyday practice, the non-recognition of the nurse's work, clerical work at the expense of care, and institutional issues. It is noticed that the experience of moral distresse in hospitals removes nurse his acting role, dismissing their practice, putting it in invisibility each other and the "I" in that it does not recognize in their work, given that the institution does not devises ways so that it develops a professional practice consistent with what he expected